Occupational Exposure of Employees in a Multispecialty Hospital to Factors Causing Contact Dermatitis—A Questionnaire Study - Aneta Drozdowska; Piotr Drozdowski; Aleksander Jaworski; Anna Ryczek; Daniel Bula; Dawid Adamczyk; Jowita Adamczyk; Ada Łątkowska; Barbara Sławińska; Adam Reich (Medicina, 2023)
Background and Objectives: Allergic contact dermatitis (ACD) is a serious health and socio-economic problem. Accurate and reliable assessment of exposure to ACD factors in the work environment would increase quality of life and work of employees. The aim of this study was to assess the level of exposure of workers of a multidisciplinary hospital to the factors causing ACD. Material and Methods: The proprietary OSDES-16 questionnaire was used. The effectiveness of the OSDES-16 was confirmed statistically. The study included 230 employees of the medical center in Polanica Zdrój, divided into groups. Results: The differences in the overall assessment of exposure between the individual groups in the OSDES-16 scale were statistically insignificant (p > 0.05). There was no significant correlation between the current workplace and the level of exposure to ACD (p > 0.05). The level of exposure to ACD in the group of employees with work experience in the current position for more than 10 years was significantly higher than those working less than 6 years (p < 0.05). Conclusions: Nurses, midwives and paramedics are the occupational group most exposed to the development of contact allergy related to exposure to factors present in the work environment. The seniority of more than 10 years in the current position was linked with a higher level of occupational exposure.